A two-phased perishable inventory model for production planning in a food industry. (July 2019) - Shin, Moonsoo; Lee, Hwaseop; Ryu, Kwangyeol; Cho, Yongju; Son, Young-Jun
Highlights: Perishable inventory can be controlled with cost-free renewability. A generic solver cannot guarantee feasibility considering perishability. Initial inventory has been considered for relaxation of infeasible condition. The extended heuristics proposed guarantees feasibility of solutions in all cases. Abstract: The food industry is faced with complicated inventory management problems because of the perishable nature of its raw materials, i.e., agricultural or marine products. Because agricultural and marine products spoil over time, it is necessary for inventory managers to employ a management strategy to prevent expiration of their storage periods. Furthermore, supply and demand of agricultural and marine products fluctuate considerably with climatic variations, seasonal changes and various social factors. Thus, a dynamic inventory model is to be devised concerning such fluctuation of supply and demand. In this paper, a two-phased perishable inventory model for a food industry is proposed, where the inventory is perishable, but can be renewed by additional processing. The proposed model is applied and demonstrated with a kimchi processing facility in Korea. Two heuristic solution methods for generating its inventory management plan are also presented along with computational experiments.